Speed Control of Switched Reluctance Motor Using Fuzzy Sliding Mode - TAHOUR, A.; ABID, H.; AISSAOUI, A. G. (Advances in Electrical and Computer Engineering, 2008)
In this paper, a fuzzy logic controller (FLC) is designed, based on the similarity between the FLC and the sliding mode control (SMC), for a class of nonlinear system to tackle the nonlinear control problems with modelling uncertainties, plant parameters variations and external disturbances. The proposed scheme gives fast dynamic response with no overshoot and zero steady-state error. To show the validity and the effectiveness of the control method, simulations are performed for the speed control of a switched reluctance motor. The simulation results show that the controller designed is more effective than the conventional sliding mode controller in enhancing the robustness of control systems with high accuracy.